2017
DOI: 10.1111/vec.12592
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of plasma cell‐free DNA concentrations in dogs with sepsis, trauma, and neoplasia

Abstract: cfDNA can be readily identified in canine plasma using 2 fluorescence assays. DNA extraction offers no advantage over direct measurement. Compared to healthy controls, dogs with sepsis or moderate-severe trauma have significantly increased plasma cfDNA concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 36 publications
(66 reference statements)
4
63
0
Order By: Relevance
“…A significant increase in the blood concentration of cfDNA was found in diseased dogs, as compared to healthy dogs, and a positive association between cfDNA concentration and disease severity and survival was observed . Both dogs with sepsis and those with moderate‐to‐severe trauma had significantly increased cfDNA concentrations compared to healthy dogs, and cfDNA concentration was associated with death in dogs with immune‐mediated hemolytic anemia …”
mentioning
confidence: 94%
See 2 more Smart Citations
“…A significant increase in the blood concentration of cfDNA was found in diseased dogs, as compared to healthy dogs, and a positive association between cfDNA concentration and disease severity and survival was observed . Both dogs with sepsis and those with moderate‐to‐severe trauma had significantly increased cfDNA concentrations compared to healthy dogs, and cfDNA concentration was associated with death in dogs with immune‐mediated hemolytic anemia …”
mentioning
confidence: 94%
“…19,20 The ability to detect cfDNA in canine blood led to the investigation of cfDNA in other disease states. 21,22 A significant increase in the blood concentration of cfDNA was found in diseased dogs, as compared to healthy dogs, and a positive association between cfDNA concentration and disease severity and survival was observed. 21 22 and cfDNA concentration was associated with death in dogs with immune-mediated hemolytic anemia.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In the past, cfDNA was thought to originate largely from cells undergoing apoptosis or necrosis, but in recent years, it has been suggested that DNA might also be released from living cells . Plasma concentrations of cfDNA are increased in various disease states in dogs, including mammary tumors, lymphoid neoplasia, pulmonary thromboembolism, sarcomas, trauma, and sepsis . However, as for NT‐proBNP, the effect of prolonged strenuous exercise on plasma cfDNA concentrations in dogs is unknown.…”
mentioning
confidence: 99%
“…17,18 Plasma concentrations of cfDNA are increased in various disease states in dogs, 19 including mammary tumors, 20,21 lymphoid neoplasia, 22 pulmonary thromboembolism, 23 sarcomas, trauma, and sepsis. 24 However, as for NT-proBNP, the effect of prolonged strenuous exercise on plasma cfDNA concentrations in dogs is unknown.…”
mentioning
confidence: 99%